To tweet or not to tweet? Exploring the effectiveness of service recovery strategies using social media. Issue 9 (5th September 2016) - Fan, Ying; Niu, Run Hong
Abstract : Purpose: The purpose of this paper is to explore influencing factors that affect the effectiveness of service recovery strategies using social network from operations management perspective. Specifically, the authors study the relationships between social media agent responses to customer complaints, customer emotion changes and customer satisfaction. Furthermore, the authors investigate the roles of recovery speed and failure severity in the service recovery process using social network platform. Design/methodology/approach: The results are based on 347 mini cases drawn from the Twitter accounts of a sample of airlines. Grounded theory approach is used to conduct qualitative analysis using NVivo 9, a qualitative data analysis program. A conceptual framework was developed, then tested using χ 2 analysis. Findings: Agent responses that do not require customers to take further initiatives for problem solving have positive effects on customer emotion alleviation and satisfaction. In contrast, responses that provide further directions poses negative effect on service recovery outcomes. There is a strong positive linkage between customer emotion change and customer satisfaction. Surprisingly, the direct effect of recovery speed on customer emotion and satisfaction is not supported by the data. Rather, it plays a moderating role in affecting the relationship between agent responses and customer satisfaction. The qualitative data further reveals the pivotal role of failure severity, one of key service failure attributes. Research limitations/implications: The authors study service businesses' recovery strategies using social media. A conceptual framework is developed to link agent responses, customer emotion changes and customer satisfaction from the lens of service providers, using an operations-oriented approach. Finding on recovery speed and failure severity reveal that these variables play different roles when service recovery is operated on social media platform as compared to traditional channels. Additionally, relying on tweets as data sources has constrained us from assessing other long-term service recovery outcomes such as loyalty, repurchase intent and word of mouth. The drawback is resulted from the limited information conveyed through tweets, which tends to be short and brief. The study focusses on the airline industry, which limits the generalizability of the findings to other service industries. Practical implications: The authors highlight the value and potential of service recovery strategies using social network and provide insights for recovery operations where agent responses should be focussing on real time problem solving. The findings support the benefits of empowering social network agents for service recovery operations. Improving recovery speed should be less of a priority as it serves as a qualifier when service recovery is operated via social network. Given the pivotal role of failure severity, it is critical for social network agents to stand in the shoes of the complaining customers, making imminent assessment of the actual failure severity and taking action accordingly in real time. In the meantime, effective communication through social network may help to lower perceived magnitude of failure by customers, which in turn enhance the effectiveness of other service recovery efforts. Originality/value: This study is the first attempt to investigate the service recovery process using social media from an operations-oriented perspective. The results supports the potentials of employing service recovery strategies using social media.